A Real-Time Semiautonomous Audio Panning System for Music Mixing. (26th May 2010) - Perez_Gonzalez Perez_Gonzalez, Enrique Enrique; Reiss Reiss, Joshua D. Joshua D.
Abstract : A real-time semiautonomous stereo panning system for music mixing has been implemented. The system uses spectral decomposition, constraint rules, and cross-adaptive algorithms to perform real-time placement of sources in a stereo mix. A subjective evaluation test was devised to evaluate its quality against human panning. It was shown that the automatic panning technique performed better than a nonexpert and showed no significant statistical difference to the performance of a professional mixing engineer.